Satire in post-independence African plays: A study of Efo Kodjo Mawugbe’s Prison Graduates (2015) - Essuman, Jonathan; Ben-Daniels, Faith; Ohene-Adu, Kingsley Brempong (Research Journal in Advanced Humanities, 2021)
Post-independence African plays have been characterized by the disillusionment of playwrights with African reality. Corruption, which is chiefly political, and of other forms, and other pertinent neo-colonial issues have been religiously dealt with by these writers in their creative works. Through the tents of postcolonial theory, this article attempts to analyze Efo Kodjo Mawugbe’s Prison Graduates as a satire. A normative research method, which is based entirely on the impressionistic observations of the investigator was used in the data collection. Practically, satire has rightly become a preferred form of writing for various writers to express their disillusionment. In his text, Mawugbe uses satire to create a real African world which looks beyond foreign aids in order to claim African dignity and identity.